Reúso adaptativo cómo estrategia de diseño de vivienda social en Ambato - Rodríguez López, Luis Angel (2024)
The present work examines the problem of generalized deterioration and underutilization that a large number of buildings in the city center of Ambato present, a situation that entails a series of inconveniences that affect the urban dynamics, such as the growth of informality, the housing deficit and the existence of numerous spaces that are not adapted to the contemporary habitability needs of this specific spatial and temporal context. Likewise, it raises the parallel situation that the construction industry continues to have a very high demand for natural and energy resources in order to develop its activity, with the consequent generation of a large ecological footprint derived from the high environmental impact that this means. Faced with this complex panorama, the present research work proposes and thoroughly analyzes the adaptive reuse of those buildings that are currently in a situation of disuse or deterioration. The detailed methodological design that this research follows to meet its objectives is mentioned, noting that it is a qualitative and exploratory-descriptive research. Various analysis tools have been developed and applied, such as mappings, observation sheets, case studies and interviews with experts in the field. Finally, the last chapter contemplates the analysis carried out on the information obtained from the application of the previously defined methodological tools. The end product of this research is a guide with adaptive reuse strategies for the context of Ambato.